2018
DOI: 10.33552/wjovr.2018.01.000505
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Disease: The Undervalued Impact on Quality of Life

Abstract: Dry eye disease (DED) is one of most common ocular disease and reason for primary eye care visit worldwide. DED has gone through major evolutions over the past couple of decades. As stated in the latest DEWS II report in 2017, the definition of DED is now "a multifactorial disease of the ocular surface characterized by a loss of homeostasis of the tear film, and accompanied by ocular symptoms, in which tear film instability and hyperosmolarity, ocular surface inflammation and damage, and neurosensory abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Visual disturbance is also a common symptom seen in patients with DED. It affects the quality of life (QoL) and visual performance in 11,12 patients. Studies reported that DED has an impact on a patient's QoL such as ability to perform certain activities that require continuous visual attention like reading and driving.…”
Section: Dry Eye Disease By Academic Yearmentioning
confidence: 99%
“…Visual disturbance is also a common symptom seen in patients with DED. It affects the quality of life (QoL) and visual performance in 11,12 patients. Studies reported that DED has an impact on a patient's QoL such as ability to perform certain activities that require continuous visual attention like reading and driving.…”
Section: Dry Eye Disease By Academic Yearmentioning
confidence: 99%
“…prevalent ocular surface diseases in the world. In epidemiological studies performed globally, DED prevalence ranged from 5 to 64% (Noor, 2018;Shanti et al, 2020;Uchino & Schaumberg, 2013). DEDs prevalence in Al-Ahsa, Saudi Arabia, was found to be 32.1% (Alshammari et al, 2021).…”
mentioning
confidence: 99%